Reconstruction of The Pawn Agreement Based on Justice - Wasana, Budi; Nasution, Krisnadi; Latumahina, Rosalinda Elsina (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Legally, the clauses in the pawn agreement still contain clauses that conflict with the Consumer Protection Law Nomor 8 of 1999 Article 18 paragraph (1) letter a which states that business actors who offer goods and/or services intended for trading are prohibited from making or including standard clauses in each document and/or agreement if: they state the transfer of responsibility of the business actor. In the pawn agreement there are still missing clauses that should be included in the pawn agreement.Purposes of the Research: To analyze and find a reconstruction of the mortgage agreement based on justice.Methods of the Research: The research method used is normative juridical. Descriptive and argumentative techniques must be used in carrying out the analysis.Results Main Findings of the Research: Exoneration clauses are contrary to the principle of justice, therefore firm action from the authorities must be implemented without discrimination. This is done so that standard agreements made by business actors reflect the principle of justice. The purpose and objective of having a fair agreement is to get a happy ending. If an exoneration clause is found in the agreement, in this case a pawn agreement, then it is necessary to reconstruct the agreement. So that a just and civilized humanitarian agreement and social justice for all Indonesian people are realized.